The Great China Carbon Trading: Political Economy of Climate Change Governance - Wahyu Indriyadi (Mengeja Indonesia Publisher, 2022)
This study aims to analyze the political economy aspect of carbon trading markets in China and how it will influence climate change governance. It is essential to understand the underpinning political economy aspects of emerging carbon trading markets in China because China will operate the world’s largest carbon market. China’s work on carbon trading represents higher requirements for China’s national industries and a higher commitment to addressing climate change. This study uses an exploratory qualitative approach to examine the history of carbon trading in China, its political economy aspects, and how China's carbon trading can significantly contribute to climate change. When China launched its national carbon trading scheme in 2021, the size of China's carbon trading became the world's most extensive climate policy scheme. This study shows that China’s rigorous environmental policy experimentations to gradually establish carbon trading by implementing the CDM projects, setting up regional carbon trading pilots in six cities, finalizing regulations, and establishing a mechanism for national carbon trading have been successful. The prospect and potential of China's carbon trading are enormous, considering the size of the CDM projects in China, China’s position as one of the largest emitters in the world, and the scale of industries included in the national carbon trading scheme in China. However, there are still uncertainties in the prospect of carbon trading in China, historically weak climate policy enforcement, and misreporting of data that can affect the integrity of China’s calculation.